Volumen Cardiaco: en el nativo normal de altura en el portador de soroche crónico y en el individuo normal de nivel del mar - MARTICORENA, E. (2024)
Utilizing a radiologic thecnicbased on the Eclipse Method it has been investigated the cardiad volume (CV) of normal high altitude natives, patients of chronic mountain sicknes (CMS) living at 4,340 mts. ab.s.l. and normal residents at sea level. The C. V. of high altitude normal individual were higher compared with normal resident at5/L, however, this difference were not significant. The mean value of CV or CMS patients were significantly higher than those encountered at normal high lands residents.Correlation of CV and hematocrit, blood volume, systemic and pulmonar pressure were explored. The only significative correlation foundwas the pulmonar pressure.The slight difference between the CV of high altitude and sea leve/ residents, may be consequence to the systolic type of the right ventricular overload, which produces concentric type of the ventricular hypertrophy rather thandilation. The higher values of the CV in patients with CMS should be explained by the higher degree of pulmony pressure and presumibly by myocardic anoxia, subsequent to severe arterial unsaturation.